Whale Watching in the Pelagos Sanctuary: Status and Quality Assessment - Tepsich, Paola; Borroni, Anna; Zorgno, Margherita; Rosso, Massimiliano; Moulins, Aurélie (Frontiers in Marine Science, 2020)
In 2001 Italy, France and Principality of Monaco instituted a protected area for marine mammals in northwestern Mediterranean Sea, named the Pelagos Sanctuary. The agreement foresees the commitment by signing parties to manage human activities in the area, with a special mention to whale watching. Whale watching is a form of wildlife tourism which has considerably grown in the last decades. Understanding the profile of whale watchers and their satisfaction towards the activity, is the first step toward a sustainable and effective management of this touristic activity. In this work we provide the first analysis of the whale watching activity in the Pelagos Sanctuary, focusing on commercial whale watching tours departing from Italian harbors in Liguria. We provide a census of the activity and the results of close-ended questionnaires filled by whale watchers during trips in summer 2016 and 2017. The aim of the questionnaires was to understand the level of awareness of experienced and new whale watchers regarding the Pelagos Sanctuary and some conservation initiative going on in the area. Finally, we analyzed the satisfaction level, with the aim of evidencing weakness and strengths of the service offered. Our results evidence a growth in the activity in the last 15 years, with a wider differentiation of offers and impacting a larger area than previously found. Whale watchers in the area come from a variety of countries, demonstrating the importance of the Pelagos as a hot spot for this activity. A high level of satisfaction has been evidenced, with no difference among new and experienced whale watchers. At the same time, more effort is needed to increase awareness of Pelagos and its conservation initiative both at a national and international level. This study provides useful information for the start of an effective management of whale watching in this protected area.